Challenges and Opportunities in Implementing the Teaching Factory Model in Special Needs Schools: Alternative Work Readiness for Students with Disabilities - Aprilia, Imas Diana; Tarsidi, Iding; Rahmat, Cece; Hernawati, Tati (Department of Special Education, 2025)
The intense job competition and the low absorption rate of special needs school graduates in the business and industrial sectors are allegedly due to the ineffective implementation of the link-and-match concept. This study aims to analyze the challenges and opportunities faced by special needs schools in preparing students for the workforce through the Teaching Factory (TEFA) model. Using a descriptive qualitative method, data were collected from two principals and six vocational skills teachers through interviews, observations, and document analysis. The results indicate that teacher competence in mastering vocational skills remains low, the curriculum oriented toward Competency-Based Training (CBT) and Production-Based Training (PBT) has not been properly accommodated, and infrastructure and financial resources are limited. However, several opportunities were identified, including principals’ good understanding of the TEFA concept, extensive partnerships with related institutions (Vocational High Schools and industries), vocational skills programs developed based on needs assessments, and vocational skills roadmaps aligned with school visions and missions. The study concludes that the main challenges faced by special needs schools revolve around human resources, financial resources, service programs, and infrastructure, while opportunities exist in human resources and service programs. These findings highlight that special needs schools continue to face significant obstacles in effectively implementing the TEFA model to prepare students for employment. Therefore, a proper and comprehensive analysis is necessary to identify operational strategies that can minimize challenges and maximize opportunities for special needs education in implementing an adaptive and accommodating TEFA model.